1989
DOI: 10.1002/ajmg.1320340409
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive behavior in the fra(X) syndrome: A longitudinal study in eight patients

Abstract: In this study we investigated the development of adaptive behavior of 8 fragile X [fra(X)] males with special attention to social competence and compared the results with a control group of 8 fra(X) negative males matched for age, level of adaptive functioning, and period of institutionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Some studies report the event as a "plateau" of ageequivalent scores [Dykens et al, 1993[Dykens et al, , 1996 or as scores of differing dimensions of adaptive behavior [Wiegers et al, 1993]. Others portray a negatively accelerating function of composite scores that reach a minimum during adolescence [Curfs et al, 1989;Fisch et al, 1994Fisch et al, , 1996b. We examined three domains of adaptive behavior and found that communication domain scores were the most severely impacted and they plateau earlier than either socialization domain or daily living skills scores, as reported previously in cross-sectional and retrospective longitudinal studies [Dykens et al, 1993[Dykens et al, , 1996Wiegers et al, 1993].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Some studies report the event as a "plateau" of ageequivalent scores [Dykens et al, 1993[Dykens et al, , 1996 or as scores of differing dimensions of adaptive behavior [Wiegers et al, 1993]. Others portray a negatively accelerating function of composite scores that reach a minimum during adolescence [Curfs et al, 1989;Fisch et al, 1994Fisch et al, , 1996b. We examined three domains of adaptive behavior and found that communication domain scores were the most severely impacted and they plateau earlier than either socialization domain or daily living skills scores, as reported previously in cross-sectional and retrospective longitudinal studies [Dykens et al, 1993[Dykens et al, , 1996Wiegers et al, 1993].…”
Section: Discussionsupporting
confidence: 61%
“…Like studies of cognitive deficits, early crosssectional investigations of adaptive behavior in fra(X) males found negative correlations between chronological age and adaptive behavior composite scores [Curfs et al, 1989;Fisch et al, 1994] or noted that ageequivalent scores of adaptive behavior leveled off as chronological age increased [Dykens et al, 1993]. Therefore, cognitive ability and adaptive behavior reach an asymptote as young fra(X) males age.…”
Section: Introductionmentioning
confidence: 98%
“…Longitudinal decreases in IQ have been observed previously in male fra(X) children and adolescents. Declines in SQ have been observed primarily in adolescent fra(X) males [Curfs et al, 1989b;Dykens et al, 19931, although Wiegers et al [1993] show no relationship between age and adaptive score. It may be that the SRZ used by Wiegers et al draws upon a different set of behaviors than the VABS.…”
Section: Discussionmentioning
confidence: 99%
“…Work identifying endophenotypes in FXS has demonstrated behavioral deficits across the domains of spatiotemporal processing, numerical or arithmetic processing, to some extent executive function, and specific visual biological motion processing abnormalities (Bregman et al , 1987; Curfs et al , 1989a, 1989b, 1989c; Dykens et al , 1987; Mazzocco et al , 1993; Van der Molen et al , 2010). In the spatiotemporal domain, there have been reports of specific deficits in spatial and temporal memory performance in FXS, even in cases where FSIQ is controlled as a covariate and verbal performance is equal to or surpasses that of controls ( cf.…”
Section: Specific Examplesmentioning
confidence: 99%